SIALANG - Agung Gumelar (Saraswati)
Sialang is an ethnical music performance inspired by honey bees collecting nectars. The idea evolved into a concept of life that comprises three elements of the interacting and interdependent creatures. Sialang is a tree that shelters the bees until they produce honey; from early life into adulthood, they are persistent to deal with natural selection and to survive amidst the challenges they are facing such as bad weather, attacks from other animals, and uncertain climate. From the life they had never live before until the life with full of threats to their survival. Therefore, human, plant and animal should establish a mutually beneficial life in order to realize a harmonious life. Such phenomenon is manifested because of the tangle of three elements that play a major role in fostering a mutually beneficial relationship. The one and the other elements are welded together to form a unified whole. This phenomenon can be expressed in the form of intertwining circles as the food chain that works on a cyclical basis in an ecosystem.   Keywords: honey, concept of life, Sialang.